2020
DOI: 10.1016/j.euo.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Node-positive Prostate Cancer at Radical Prostatectomy and Pelvic Lymph Node Dissection: A Systematic Review

Abstract: Introduction:The optimal management of prostate cancer (PCa) patients with lymph node invasion (LNI) at radical prostatectomy (RP) and pelvic lymph node dissection (PLND) still remains unclear.Objective: To assess the effectiveness of postoperative treatment strategies for pathologically node-positive PCa patients. The secondary aim was to identify the most relevant prognostic factors to guide the management of pN1 patients. Evidence Acquisition: A systematic review was performed in January 2020 using Medline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 43 publications
4
35
0
Order By: Relevance
“… 20 , 21 , 22 However, due to the different natural history of radiation‐recurrent PCa undergoing SRP, data from primary radical prostatectomy cannot be extrapolated to radiation‐recurrent PCa patients planned for SRP. 16 , 17 , 23 In a report from the Surveillance, Epidemiology, End Results registry (SEER) evaluating 364 patients who underwent SRP between 1988 and 2010, Pokala et al 24 did not find a significant association between the number of RLNs and cancer‐specific survival (HR 0.5, 95% CI: 0.2–1.4, p = .2). 24 However, a more recent analysis of the SEER database which included patients who were treated between 2004 and 2016, Wenzel et al 25 did demonstrate a significantly lower cancer‐specific mortality with a higher number of removed nodes (HR: 0.61, CI: 0.40–0.91; p = .02).…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 , 22 However, due to the different natural history of radiation‐recurrent PCa undergoing SRP, data from primary radical prostatectomy cannot be extrapolated to radiation‐recurrent PCa patients planned for SRP. 16 , 17 , 23 In a report from the Surveillance, Epidemiology, End Results registry (SEER) evaluating 364 patients who underwent SRP between 1988 and 2010, Pokala et al 24 did not find a significant association between the number of RLNs and cancer‐specific survival (HR 0.5, 95% CI: 0.2–1.4, p = .2). 24 However, a more recent analysis of the SEER database which included patients who were treated between 2004 and 2016, Wenzel et al 25 did demonstrate a significantly lower cancer‐specific mortality with a higher number of removed nodes (HR: 0.61, CI: 0.40–0.91; p = .02).…”
Section: Discussionmentioning
confidence: 99%
“…According to the previously published data, adverse pathological features in prostate cancer include positive resection margin, seminal vesicle invasion, and extracapsular extension [22,23]. In particular, Gleason score � 8 and a high number of positive nodes in LNP prostate cancer are also known as aggressive pathologic characteristics [5]. However, most of the pathological factors that were examined in this study were not significantly related to the outcomes of salvage treatment for LNP prostate cancer.…”
Section: Plos Onementioning
confidence: 65%
“…Of all prostate cancer patients who receive RP and pelvic lymph node dissection (PLND), 3-14% have pathological lymph node-positive (LNP) disease [1][2][3]. Several previous studies showed that LNP was associated with poor prognosis in prostate cancer patients who received RP as initial treatment [4][5][6]. Nonetheless, the optimal management of patients with LNP still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear, however, if ePLND should still be based on a nomogram calculation of an individual’s risk of LNM or PSMA PET-CT findings alone. Traditionally, PLND is considered only valuable for prognosis as correctly identified pN1 patients typically benefit from adjuvant therapies [ 51 ]. This is supported by research that has failed to demonstrate an oncological benefit for lymphadenectomy or its extent [ 52 , 53 ].With the new lens of PSMA PET-CT, new studies have demonstrated 50% of suspected LNM lie outside the boundary of ePLND [ 54 ].…”
Section: Eplnd In the Era Of Psma Pet-ctmentioning
confidence: 99%